Appointment attendance in patients with schizophrenia. (July 2014) - Daniels, Karin; Loganathan, Muruga; Wilson, Rose; Kasckow, John
We conducted a review of recent studies of appointment attendance in patients with schizophrenia. Appointment attendance is identified as an important issue, but the amount of attention addressing it is limited. Rates of missed appointments in the studies reviewed range from 20 to 67%. The transition from inpatient to outpatient care appears to be a time of higher rates of missed appointments. Correlates of missed appointments vary greatly across studies, with the most consistent relationship found between increased levels of psychopathology and decreased appointment attendance. Review of the limited literature on the relationship between missed appointments and suicide in patients with schizophrenia reveals an increase in mental health contacts prior to and following suicidal behaviors. Interventional studies demonstrate that appointment attendance can be improved. Psychoeducation and appointment reminders show promise in improving attendance. Future research on appointment attendance is likely to be facilitated by the use of emerging technologies.